An investigation into the optimal granular sludge size for simultaneous nitrogen and phosphate removal. (15th June 2021) - Nguyen Quoc, Bao; Armenta, Maxwell; Carter, John A.; Bucher, Robert; Sukapanpotharam, Pardi; Bryson, Samuel J.; Stahl, David A.; Stensel, H. David; Winkler, Mari-Karoliina H.
Highlights: Determination of the optimal granule size for SND and phosphorus removal across different DO values. Within DO 2–4 mg/L, granular size had a greater effect on nutrient removal than increasing DO. In big granules, nitrogen removal was limited by nitrification rate. <1000 µm granules had highest nitrification rate and specific nitrogen removal rates. >1000 µm granules had higher abundance of nir gene but showed lower specific nitrogen removal rates. Abstract: An aerobic granular sludge (AGS) pilot plant fed with a mixture of acetate amended centrate and secondary effluent was used to investigate the optimal granule size range for simultaneous nitrification and denitrification (SND) and ortho-phosphate removal. The anaerobic phase was mixed to understand how AGS will perform if integrated with a continuous flow activated sludge system that cannot feed the influent through the settled sludge bed. Five different granule size fractions were taken from the pilot (operated at DO setpoint of 2mgO2 /L) and each size was subjected to activity tests in a well-controlled lab-scale AGS reactor at four dissolved oxygen (DO) concentrations of 1, 2, 3, and 4 mgO2 /L. The size fractions were: 212 – 600 µm, 600 – 1000 µm, 1000 – 1400 µm, 1400 – 2000 µm, and >2000 µm. The smallest size range (212 – 600 µm) had the highest nitrification and phosphate removal rates at DO setpoints from 1 – 3 mgO2 /L, which was attributed to the higher aerobic volume fraction in small granules and hence a higher abundance of phosphorus accumulating organisms (PAO) and ammonia oxidizing bacteria (AOB). In comparison, large granules (>1000 µm) had 1.4 – 4.7 times lower ammonia oxidation rates than the smallest size range, which aligned with their lower AOB abundance relative to granule biomass. The granules with the highest anoxic volume fraction had the highest abundance of nitrite reductase genes ( nir gene) but did not show the highest specific nitrogen removal rate. Instead, smaller granules (212 – 600 and 600 – 1000 µm), which had a lower nir gene abundance, had the highest specific nitrogen removal rates (1.2 – 3.1 times higher than larger granules) across all DO values except at 4 mgO2 /L. At a DO setpoint of 4 mgO2 /L, nitrite production by ammonia oxidation (ammonia monooxygenase) exceeded nitrite reduction by nitrite reductase in granules smaller than 1000 µm, in addition, some denitrifying heterotrophs switched to oxygen utilization in deeper layers hence suppressing denitrification activity. At the DO range of 2 – 4 mg/L, granular size had a greater effect on nutrient removal than DO. Therefore, for AGS developed at an average DO setpoint of 2 mgO2 /L, selecting for size fractions in the range of 212 – 1000 µm and avoiding DO values higher than 3 mgO2 /L can achieve both a higher nitrogen removal capacity and energy savings. This study is the first to investigate the influence of different DO values on SND and biological phosphorus removal performance of different aerobic granular sludge sizes. Graphical abstract: Image, graphical abstract